Revitalisasi Nilai-Nilai Hukum Perkawinan Masyarakat Konjo Bulukumba Dalam Mencegah Disintegrasi Keluarga Perspektif Maqashid Al Syariah: The Perspective of Maqashid Al Syariah - Amalia, A. Vivi; Andika, Holis; Fajriwahyuningsi, Andi (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
Marriage in the Konjo Bulukumba community has social and spiritual values that serve to maintain family integrity, but globalization poses challenges in the form of increased potential for family disintegration and the weakening of traditional values. This study aims to analyze the legal values of marriage in the Konjo community, their implementation in preventing divorce, and their relevance to the principles of maqāṣid al-syarī‘ah. This study uses a qualitative approach with a sociological-empirical method. Data were obtained through field observations, in-depth interviews with four informants selected purposively (traditional leaders, religious leaders, and married couples), and documentation review, then analyzed using an interactive model through a process of reduction, presentation, and conclusion drawing. The results of the study show that the practice of pudeppo (traditional advice before marriage), the involvement of the extended family in resolving domestic conflicts, and an emphasis on responsibility and mutual cooperation are effective cultural instruments in reducing divorce rates while maintaining social solidarity. From the perspective of maqāṣid al-syarī‘ah, these values are in line with the objectives of protecting religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), offspring (ḥifẓ al-nasl), and property (ḥifẓ al-māl). These findings confirm that the marriage practices of the Konjo community not only function as a customary mechanism but also have a normative basis in Islamic law. Academically, this research enriches the study of marriage law based on local wisdom integrated with Sharia principles, while practically it can be a reference for traditional leaders, religious leaders, and local governments in formulating policies to preserve cultural values of marriage that support family resilience in the contemporary era.